Pengaruh Mobilisasi Dini Terhadap Intensitas Nyeri Pada Pasien Post Operasi Sectio Caesarea Di RSIA Rosiva Medan - Panjaitan, Jesica Lasma; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2025)
Postoperative pain is a physiological condition, yet it remains one of the most feared complaints among patients after surgery. Early mobilization plays an important role in reducing pain by diverting the patient’s focus away from the site of pain or surgical area, decreasing the activation of chemical mediators involved in the inflammatory process that heighten the pain response, and minimizing the transmission of pain signals to the central nervous system. The aim of this study was to determine the effect of early mobilization on pain intensity in post–cesarean section patients at RSIA Rosiva Medan. This study used a pretest and posttest control group design. The population consisted of post–cesarean section patients at RSIA Rosiva Medan. The sampling technique used was purposive sampling. The total sample in this study was 41 respondents in the intervention group and 41 respondents in the control group. Observation sheets and early mobilization SOPs were used for data collection. Data were analyzed using univariate and bivariate analyses with the Mann–Whitney test. The study showed that after early mobilization, most respondents in the intervention group experienced mild pain, totaling 34 respondents (82.9%). Meanwhile, in the control group, where early mobilization was not performed, most respondents experienced moderate pain, totaling 37 respondents (90.2%). The Mann–Whitney test yielded a p-value of 0.000. It is concluded that there is an effect of early mobilization on pain intensity in post–cesarean section patients at RSIA Rosiva Medan in 2021. It is suggested that it can be used as input for developing Standard Operating Procedures for non-pharmacological interventions to reduce pain intensity in post–cesarean section patients.